Efektivitas Penerapan Software Swansoft CNC Simulation Terhadap Hasil Belajar Psikomotorik Siswa pada Elemen Teknik Pemesinan Nonkonvensional di SMK : The Effectiveness of The Application of Swansoft CNC Simulation Software to Students' Psychomotor Learning Outcomes on Nonconventional Machining Engineering Elements at SMK - Pandu Andariansyah; C Rudy Prihantoro; Hari Din Nugraha (Jurnal Pendidikan Teknik Mesin Undiksha, 2025)
This research aims to test the level of effectiveness of the application of swansoft simulation software in improving students' psychomotor learning outcomes in the elements of non-conventional machining engineering materials for CNC lathe operation materials at SMKN 4 Tangerang. This study uses a type of quasi-experimental design research method in the form of a noneequivalent control group design. The 54 students of SMKN 4 Tangerang phase F Machining for the 2024/2025 school year were used as research samples taken using the saturated sampling technique. The data collection technique in this study uses a performance test. The data analysis technique in this study used a normality test, a homogeneity test, and a test of the average similarity of students' initial ability, then the final analysis used the t-test and the n-gain test. The results of the study show that: 1) There was no significant difference in students' psychomotor learning outcomes between the experimental class that applied the swansoft simulation software and the control class that applied teaching aids in the form of CNC lathes as a learning medium, in the t-test analysis, it was obtained -t table (-2.007) ≤ t count (-0.1) ≤ t table (2.007); 2) The application of Swansoft CNC Simulation software is quite effective in improving the psychomotor learning outcomes of phase F students of Machining on non-conventional machining engineering elements of CNC lathe operation materials at SMKN 4 Tangerang, in the analysis of the n-gain test, the average n-gain value of the experimental class was obtained of 0.613 or 61.3%.